An Analysis Of The Phrases Use On Writing Descriptive Text At The Tenth Grade Of SMK N 3 Medan - Rosalia Sugiati Pasaribu; Usman Sidabutar; Sahlan Tampubolon (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to analyze the use of phrases in writing descriptive texts produced by the tenth-grade students of SMK N 3 Medan, particularly Class X KI 3 of the Chemical Industry major. The objectives of this research are to identify the types of phrases used by the students and to determine the dominant type of phrase found in their descriptive writing. This research applied a qualitative descriptive design. The data were collected from students’ written descriptive texts. The technique of data analysis was based on Miles and Huberman’s interactive model, which consists of data condensation, data display, and conclusion drawing/verification. The findings of the study reveal that the students used several types of phrases in their descriptive texts, namely noun phrases, verb phrases, adjective phrases, and prepositional phrases. Among these types, noun phrases were dominantly used by the students in constructing descriptive texts. This indicates that students tend to focus on describing objects, people, and places by using noun-centered constructions. However, the use of other phrase types was relatively limited, which shows that students still lack syntactic variety in their writing. In conclusion, the use of phrases plays a crucial role in constructing clear and detailed descriptive texts. The dominance of noun phrases reflects the nature of descriptive writing, yet students need further guidance in using various phrase types to improve sentence complexity and writing quality. Therefore, it is recommended that English teachers provide more focused instruction and practice on phrase structures to enhance students’ grammatical competence and writing skills.